2020
DOI: 10.1111/1462-2920.15069
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum‐associated degradation mediated by MoHrd1 and MoDer1 is pivotal for appressorium development and pathogenicity of Magnaporthe oryzae

Abstract: Most secretory proteins are folded and modified in the endoplasmic reticulum (ER); however, protein folding is error-prone, resulting in toxic protein aggregation and cause ER stress. Irreversibly misfolded proteins are subjected to ER-associated degradation (ERAD), modified by ubiquitination, and degraded by the 26S proteasome. The yeast ERAD ubiquitin ligase Hrd1p and multispanning membrane protein Der1p are involved in ubiquitination and transportation of the folding-defective proteins. Here, we performed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 93 publications
(116 reference statements)
0
10
0
Order By: Relevance
“…Unfolded or misfolded proteins accumulated in ER are degraded by ER‐associated protein degradation (ERAD) through 26S proteasomes (Tang et al ., 2020). FonNst2 C171W ‐GFP, FonNst2 C263G ‐GFP, FonNst2 C326S ‐GFP, FonNst2 C171W/C263G ‐GFP, FonNst2 C171W/C326S ‐GFP, FonNst2 C263G/C326S ‐GFP and FonNst2 C171W/C263G/C326S ‐GFP in ΔFonNst2 were hardly detectable in immunoblotting assays.…”
Section: Resultsmentioning
confidence: 99%
“…Unfolded or misfolded proteins accumulated in ER are degraded by ER‐associated protein degradation (ERAD) through 26S proteasomes (Tang et al ., 2020). FonNst2 C171W ‐GFP, FonNst2 C263G ‐GFP, FonNst2 C326S ‐GFP, FonNst2 C171W/C263G ‐GFP, FonNst2 C171W/C326S ‐GFP, FonNst2 C263G/C326S ‐GFP and FonNst2 C171W/C263G/C326S ‐GFP in ΔFonNst2 were hardly detectable in immunoblotting assays.…”
Section: Resultsmentioning
confidence: 99%
“…As the concentration of H 2 O 2 increased, the inhibition rates of all the strains were also increased, but that of Δ Cfgcn5 was still significantly higher than that of WT and Δ Cfgcn5 / CfGCN5 ( Figures 7A,B ). The recent studies showed that pathogens also face host-derived ER stress during infection ( Tang et al, 2020 ; Yin et al, 2020 ). We thus used DTT to mimic ER stress derived from plants.…”
Section: Resultsmentioning
confidence: 99%
“…Disruption of certain proteins involved in the conventional ER-to-Golgi secretory pathway could affect effector secretion, morphogenesis, and pathogenicity in phytopathogenic fungi ( 41 43 ). Apoplastic effector secretion relies on the conventional fungal ER-to-Golgi secretory pathway in M. oryzae .…”
Section: Discussionmentioning
confidence: 99%